Detection of Salmonella spp. in oysters by PCR. - Bej, A K (1994)
PCR DNA amplification of a region of the himA gene of Salmonella typhimurium specifically detected Salmonella spp. In oysters, 1 to 10 cells of Salmonella spp. were rapidly detected by the PCR following a pre-enrichment step to increase sensitivity and to ensure that detection was based on the presence of viable Salmonella spp.